Implementing the Merdeka Curriculum in History Education: A Case Study of Pedagogical Transition in Post-Colonial Indonesia - Ihdha Tantri; R Soeharso; Hany Nurpratiwi (Indonesian Journal of History Education, 2026)
Abstract: This study critically examines the implementation of Indonesia's Merdeka (Independent) Curriculum in history education at SMA Negeri 1 Kragan, investigating the disjuncture between policy aspirations and classroom practice within a post-colonial educational context. Drawing on qualitative case study methodology, the research reveals that while the curriculum offers progressive pedagogical flexibility, implementation remains constrained by overlapping curricular frameworks, insufficient teacher professional development, and inadequate institutional communication networks. Teachers navigate these constraints through self-directed learning and informal collaboration, yet the absence of systematic support undermines the curriculum's transformative potential. The findings demonstrate that meaningful curriculum reform in post-colonial settings requires sustained professional development, coherent transition strategies, and recognition of teacher agency. This study contributes to international conversations about educational change in the Global South, highlighting the complex interplay between policy innovation, institutional capacity, and pedagogical practice in diverse post-colonial societies.   Abstrak: Studi ini menganalisis secara kritis penerapan Kurikulum Merdeka dalam pendidikan sejarah di SMA Negeri 1 Kragan, dengan menyelidiki kesenjangan antara retorika kebijakan dan realitas ruang kelas di tengah latar belakang pascakolonial. Dengan mengadopsi rancangan studi kasus kualitatif, penelitian ini mengungkapkan bahwa meskipun kurikulum menawarkan kebebasan pedagogis yang progresif, implementasinya terhambat oleh regulasi yang tumpang tindih, pelatihan guru yang tidak memadai, serta jaringan komunikasi yang lemah. Para guru merespons melalui upaya belajar mandiri dan kolaborasi antarsejawat, namun ketiadaan dukungan kelembagaan meredam janji transformatif kurikulum tersebut. Temuan ini menegaskan bahwa reformasi substantif dalam konteks pascakolonial memerlukan pengembangan profesional yang berkelanjutan, rencana transisi yang eksplisit, serta perhatian yang layak terhadap otonomi guru, dan dengan demikian menggarisbawahi faktor-faktor kontekstual lokal yang signifikan.